Integration of Soft Skills in Student Center Learning Methods and Student Assessment in Block 2C. Adolescent Health and Preconception - yulizawati yulizawati; Marzatia Yulika; M. Pemberdi Intasir (Journal of Midwifery, 2023)
Demand for the world of work against the criteria of candidates deemed higher. The world of work is not only a priority on academic skills (hard skills) high, but also pay attention to skills in terms of the values inherent in a person or commonly known as soft skills aspect. This capability can be referred to as non technical capabilities certainly have a role no less important than the ability academic. Soft skills taught directly by the weight of credits to student. but soft skills can be implemented in the learning process through the design system learning model based on pattern SCL / active learning.Integration of soft skills in learning are expected to improve the results of student learning outcomes. To achieve this integration softskills done in any learning method implemented in block 2C (adolescent health and preconception). Assessment MCQ only assess cognitiveÂ  not show an increase in the 2 groups were assessed. But with intergasi soft skills, show a significant improvement in the results of the results of tutorial and lab skills.It can be concluded that it is important to implement the integration of soft skills in learning